Multiculturalism In Higher Education: A Case Study Of Middle Eastern Students' Perceptions And Experiences In A Malaysian University - Pandian, Ambigapathy (Penerbit Universiti Sains Malaysia (USM Press), 2008)
Malaysia faces challenges in creating a new multi-channelled learning environment where international and local students study, connect and work with one another across classrooms, community and country borders in so many exciting ways. The Malaysian Ministry of Higher Education has made a recent move to transform the landscape of tertiary education where one main thrust aims in intensifying internationalisation and ensuring a 10%–30% enrolment of international students. Malaysian higher education will therefore experience rapid racial and ethnic diversification of its student body. This paper will examine multicultural activities that have been a part of graduate school's work for many years. There is, however, little discussion on outcomes related to diversity initiatives, multicultural programmes and global educational opportunities experienced by the students. This paper reports on the findings of a recent study that has aimed to examine diversity and multicultural awareness that influences the growth and development of graduate students. Taking the case study of Middle Eastern students in Universiti Sains Malaysia (USM), the study unveiled the patterns of interactions between international and local students which consider the quality and quantity of contact, friendship patterns, social support networks and the functional roles of inter-cultural interactions. Furthermore, the findings revealed perceptions of Middle Eastern students on the larger community which involves notions of perceived discrimination, prejudice, tolerance and stereotyping. The findings of this study would help practitioners understand the influence of student affairs programmes and services that can contribute not only to the well-being of students but also to the enhancing of multiculturalism in Malaysian higher education.